La comunicación institucional y el fortalecimiento de la imagen corporativa del Gobierno Autónomo descentralizado de mocha, periodo marzo-agosto 2017 - Tiaguaro Guamán, Edison Javier (2018)
Institutional Communication has awaked the interest of Ecuadorian public institutions, because they have realized the importance of maintaining a dynamic relationship of communication between the internal and external audience. This interrelation implies a serie of strategies that allow creating environments: of commitment, labor responsibility and self and collective improvement, complemented by environmental responsibility which help to strengthen ita image. The Institutional Communication and the strengthening oh the Gobierno Autónomo Descentralizado de Mocha´s corporative image, March - August 2017 period is a research that analyzes the Internal and External Communication of the Mocha GAD´s situation; the channels and the forms of communication that uses; the relationship between the audience and the perception of these, on the corporative image of the Institution. For this analysis, this work proposes a serie of questions like: how is the institutional communication handled in the Mocha GAD? How does it affects its internal and external audiences? Does institutional communication affects the perception of the corporative image? Issues answered and the conclusions of this research. The methodology that helped to obtain this information is structured in the following way: non-experimental, bibliographical, descriptive and field research; of qualitative-quantitative approach; and deductive - inductive method.